A Bark Beetle Hypothenemus eruditus Westwood, 1836 (Insecta: Coleoptera: Curculionidae: Scolytinae) - Yin-Tse Huang; Jiri Hulcr; Andrew J. Johnson; Andrea Lucky (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 5-page fact sheet that discusses the Hypothenemus eruditus species of the bark beetle was written by Yin-Tse Huang, Jiri Hulcr, Andrew J. Johnson, and Andrea Lucky, and published by the UF Entomology and Nematology October, July 2016.